New directions for the Portuguese higher education: Tendencies, challenges and opportunities in the road of the quality - Saraiva, M.; Reis, E. (13th Annual International Conference on Advances in Management (ICAM 2006), 2006)
Developments achieved by the industry over the last decades, either in evaluation, assurance or even in the improvement of their product’s quality, the so called “Quality Management”, came as an essential reference to the definition of quality procedures to be applied in higher education. With the Bologna process, Portuguese higher education institutions will need to appeal to methods and instruments that allow them to evaluate and guarantee their teaching quality. If a higher education institution intends to implement TQM using the Deming’s guiding principles, will have to move forward to continuous quality improvement. Usually, the quality definition is connected to satisfaction of customer’s expectations. In higher education institutions, this association is not consistent because customer's identification generates a great diversity of opinions, this being one of the first obstacles that appear in TQM implementation. This research was based in an empiric study carried out in two higher education institutions - ISCTE and the University of Évora. The main objective was to find out if the Deming’s fourteen guiding principles and the Common Assessment Framework (CAF) could be applied to Portuguese higher education institutions. The results highlight a group of potential difficulties and benefits which can be the effect of the present organizational culture of these institutions. But the implementation benefits of TQM clearly overcome the difficulties that can appear: the improvement of customer's satisfaction and the image of the organization; the efficient management and use of resources and spaces; the employees involvement in the prosecution of organization targets; the information channels improvement and communication within the organization; the creation of a community spirit, interdependence and share of values; and the increased responsibility towards the community. The study concludes that there is a strong connection between the two models - CAF and Deming’s guiding principles. This association shows that to each criteria of the CAF model there is a connection to more than one of the Deming’s guiding principles. Both models develop actions for the improvement of the organizations quality, the first one in a more general and the second one in a more detailed level.